Pengaruh Curah Hujan dan Hari Hujan terhadap Produksi Kelapa Sawit Berumur 12,15,18 Tahun di PTPN II Unit Sawit Seberang – Babalan Kecamatan Sawit Seberang Kabupaten Langkat - Cecilia Natalenta Depari; Irsal Irsal; Jonis Ginting (Universitas Sumatera Utara, 2015)
The climate factor is very influential to the growth and productivity of palm oil. Rainfall is animportant climatic element observed. Where the palm oil is a plant that requires large amounts ofwater than other crops. Purpose of this research was to determine the effect of rainfall and rain dayas well as the correlation of both on palm oil production in plants aged 12, 15 and 18 years. Thisresearch was held at PTPN II Unit Sawit Seberang–Babalan Sub-district Sawit Seberang DistrictLangkat Province of North Sumatera from March 2014 to September 2014. This research usedprimary data available in company administration. Primary data for the purposes of data analysisincludes the production of fresh fruit bunches (FFB); componen production data as total bunches,average bunches weight, and total of productive trees; rainfall data and rain day monthly in 2011,2012, and 2013 on 9 afdeling. Analysis method used are double linier regression and correlationanalysis. Model tested by classic asumption consists of normality test, heteroskedasticity test,multicollinearity, and autocorellations test by using statistic software SPSS.v.18 for windows. Theregression analysis shows that rain fall and rain day variables haven’t significant influence with alpha 5% (Sig < α 0.05) to increase the production of FFB at the age of 12, 15, and 18 years. This isbecause the rainfall is not evenly distributed throughout the year and less than optimal for thegrowth and production of FFB. From the results of the classical assumption test conducted todetermine whether the multiple regression equation feasible or not to use the regression equation toconclude that the oil palms aged 12, 15, and 18 years are qualified. Correlation results in plants was12, 15, and 18 years with two-way analysis test at 1% level showed variable rainfall and rainy dayshave a strong relationship, and the real (positive) direction. Correlation values of rainfall and rainydays are 0.895; 0.887; and 0.911 each with significant level < α 0.01. Keywords: rainfall, rain day, FFB production.